Photocatalytic activity of AgCl/SnO2 prepared by one-pot green synthesis - Pongsaton Amornpitoksuk (2020)
© 2019 Elsevier B.V. A green synthesis of AgCl/SnO2 was successfully achieved by precipitation in a natural alkaline solution extracted from wood ash. In this work, the AgCl was prepared through a reaction between Cl- ion, a counter ion from SnCl4.5H2O, and Ag+ ion from AgNO3. The products were characterized by X-ray diffractometry (XRD), transmission electron microscopy (SEM), UV–Vis diffuse reflectance spectrometry, and photoelectron spectroscopy (XPS). The presence of AgCl increased the visible light absorption ability of the AgCl/SnO2 composite and its photocatalytic activity was enhanced under visible light irradiation. Under visible light irradiation, 10%AgCl-modified SnO2 annealed at 500 °C for 1 h showed the highest photocatalytic efficiency in the degradation of rhodamine B and reactive orange dyes. The superoxide anion radical and hole were the important reactive species for dye degradation.